Degradation of chlorinated compounds by microbial communities from Sungai Ular sediments - N. I. S., Nuralhuda; Noraziah, Abu Yazid; Siti Hatijah, Mortan (AIP Publishing, 2024)
Pollution has become the biggest concern to the public due to the release of unwanted substances such as chlorinated compounds into the environment which are harmful to human health and wildlife. Agriculture activity and industrial practices actively contribute to chlorinated compounds’ discharge into Malaysia’s water sources. Anaerobic biodegradation has become one of the interesting cost-efficient and ecologically benign solutions for dealing with chlorinated compound pollution. Aerobic degradation treatment had global attention in which the oxic conditions are hard to maintain, slow process more susceptible to oxidative damage. Most of the bacteria involved in the anaerobic degradation of chlorinated compounds belong to a group called Organohalide-respiring bacteria (OHRBs). This study focused on the ability of the anaerobic bacteria sampled from the Sungai Ular sediment to degrade targeted chlorinated compounds. The anaerobic biodegradation of two different groups of chlorinated compounds which are aliphatic chlorinated alkanes (1,2-dichloroethane (1,2-DCA), 1,2-dichloropropane (1,2-DCP), chloroform (CF)) and alkene (perchloroethylene (PCE) by the Sungai Ular consortia were monitored for a certain amount of times. The results showed that the sediments of Ular River were able to degrade aliphatic chlorinated alkanes (1,2-DCA, 1,2-DCP) and alkene (PCE). The identification of the bacteria at the species level using 16S rRNA analysis was also carried out to confirm the identity of the responsible bacteria. The results showed the presence of several OHRB species in the consortia which belong to Desulfitobacterium, Desulfovibrio and Desulfomonile genus. The present research shows that the degradation of chlorinated compounds was achievable in the Sungai Ular sediment which contained several OHRB strains.